Overconfidence, Monetary Policy Committees and Chairman Dominance - Carl Andreas Claussen; Egil Matsen; Øistein Røisland; Ragnar Torvik (Norges Bank, 2009)
We suggest that overconfidence among policymakers explains why formal decision power over monetary policy is given to committees, while much of the real power to set policy remains with central bank chairmen. Overconfidence implies that the chairman underweights advice from his staff, increasing policy risk if he alone decides. A committee with decision power reduces this risk, because it induces moderation from the chairman. Overconfidence also yields disagreement and dissent in the committee, consistent with evidence from monetary policy committees. As the chairman is on average better informed, through his wider access to the staff, this would give him a suboptimal influence if policy is set through simple majority voting. Giving the chairman extra decision power, through e.g. agenda-setting rights, restores his influence. A monetary policy committee with a strong chairman balances the risks and influence distortions that occur if policymakers are overconfident.
hdl:11250/2497624
Keywords: D02; D71; E58; 330; central bank governance; monetary policy committees; overconfidence; agenda-setting